Ortega's The revolt of the masses and the triumph of the new man - Gonzalez, Pedro Blas, 1964- (Algora Pub., 2007)
This book is first and foremost a detailed and meticulous study of Ortega y Gasset's The Revolt of the Masses (1930). No other up-to-date books explore this thinker and his great work. Most importantly, the author demonstrates the relevance and importance of Ortega y Gasset's thought and his The Revolt of the Masses for today's world, showing, for instance, how Ortega's categories like mass man and decadence, have been vindicated by today's spiritual, moral and cultural decay. This aspect of the book will perhaps be of major interest to the reading public. What Ortega argues for in his brief h.